Emendas parlamentares e o financiamento da política de assistência social no Estado do Espírito Santo (2012-2019) - Araujo, Diva Aparecida Curbani (2023)
The objective of this research was to analyze the configuration of the resources of parliamentary amendments intended for social assistance in the state of Espirito Santo in the period from 2012 to 2019, aiming to problematize the direction of spending money and its implications for the organization, management and financing of this policy. The methodological path groups the literature review, documentary research, quantitative-qualitative approach and content analysis. The foundations of literature dialogue with the aspects of history, legislation and data collection for a critical reflection that points to another arena of dispute of the public fund. The results show that the financing of social assistance has been following a trajectory of decrease in the contribution of resources in relation to the state social security budget, while there is an increase in the participation of parliamentary amendments within the budget and to a greater extent from the new Regulatory Framework for Civil Society Organizations, which favored the expansion of the performance of these institutions in the execution of social policies. As a part of the financing of the state social assistance, the parliamentary amendments executed play a clientelist relationship with the Brazilian Civil Society Organization (CSO) by determining a representativity of 96% as beneficiaries in the budget law of which there is a group that stands out regarding the volume of resources and recurrence of access to the public fund. The path of budgetary resources reveals the clientelist convergence characteristic of parliamentary amendments, which exercise a functionality that interests the neoliberal project reverberated in impacts on the forms of control, regulation and financing of social assistance.